(untitled) (Research, Society and Development, 2021)
The Covid-19 pandemic presents, in addition to respiratory symptoms, symptoms of post-traumatic disorder (PTSD), anxiety and depression that are also strong, being prevalent in infected patients. integrative literature review study, focusing on descriptive, retrospective and qualitative bibliographic research based on the study, analysis and correlation of material already published to support the proposed theme and seeks to investigate the impact of the pandemic on the mental health of the population. The main highlights were: anxiety, depression, drug use, propensity to commit suicide. It was also possible to observe that emotional occurrences sometimes do not arise directly from the disease itself, symptoms and signs, but are strongly associated with all the biological, psychological and social disorders that a pandemic brought about in the last two years. it was possible to observe an increase in complaints such as: anxiety, depression, post traumatic stress. In addition to those already mentioned, an increase in drug abuse was also observed, as well as the propensity to commit suicide, and the act itself. Therefore, it is necessary for the health system to build public policies that come to serve the population in mental health after Covid-19, in addition to the dissemination of correct information about the treatment and prevention of the pathology, as the best form of prevention is health education.